Phase stability of carbon, oxygen and carbon dioxide under extreme P-T conditions, beyond the harmonic approximation (2020)
Tesis (Doctor en Ciencias Física). -- Universidad de Cartagena. Facultad de Ciencias Exactas y Naturales, 2020